Color and shadow: lighting and training in the work of a lighting designer between Minas Gerais and São Paulo. Interview with Nezito Reis (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2024)
In the interview that is now being published, which took place in a pleasant meeting with Nezito Reis at his home in Barbacena, surrounded by memories, boxes of photos, texts and materials used over the years in his stage lighting classes, we tried, by listening to his memories, to glimpse the threads and traces of possible histories of Brazilian stage lighting in the capital of São Paulo. How did a man with a passion for the theatre, who moved from the interior of Minas Gerais to the capital of São Paulo because he wanted to be an actor, become an important lighting designer and, above all, the person responsible for training many of the country's stage lighting professionals? This trajectory, which you can follow in the lines published below, is the inauguration of a project, with the same simplicity and affection that the master transmits to us, to collect the memories of our country's backstage professionals in the search for another history of our theatre. This is the basic proposition of the Centre for the Study of Techniques and Crafts of the Stage of the Research Group in History, Politics and the Stage (CNPq) of the Federal University of São João del-Rei - NETOC/GPHPC/UFSJ.
Keywords: Stage light; Teaching stage light; History of stage light; Nezito Pereira dos Reis